EFFICACY OF ACCELERATION AND ABILITY GROUPING ON ACADEMIC ACHIEVEMENT OF GIFTED STUDENTS IN SELECTED SECONDARY SCHOOLS IN MORO LOCAL GOVERNMENT AREA, ILORIN NIGERIA - Hamzat, Rasheed Alaro Adewale (PEOPLE: International Journal of Social Sciences, 2016)
The type of educational instructions expected to be delivered to the gifted students differ quantitatively from the traditional methods in general classroom settings. This is because, traditional and conventional strategies may not challenge the educational needs of the gifted. Considering the enormity of what is expected of build a qualitative education of the gifted, this study investigated the efficacy of acceleration and ability grouping on academic achievement of gifted students in selected secondary schools in Moro Local Government Area in Ilorin, Nigeria. The study used the pre-test post- test control group quasi-experimental design in a 3X2 factorial matrix. The participants for the study consisted 60 Senior Secondary School gifted students from eight secondary schools in Ilorin. The subjects were randomly assigned into three experimental groups. Analysis of Covariance was the main statistical method used to test two formulated hypotheses at the probability of 0.05. The findings revealed that there was significant mean effect of treatment on academic achievement of gifted students (F(2,53)= 32.12). There was no significant main effect of gender. The study also showed that gifted male participants exposed to Acceleration and Ability grouping teaching models had higher mean score (* = 80.83) than female counterparts exposed to the same treatment. Since Acceleration and Ability grouping models are capable of enhancing gifted students’ academic achievement, it is therefore recommended that both regular special educators should use these teaching models in enhancing the academic achievement for the precocious ones.